Molecular detection and characterisation of potentially new Babesia and Theileria species/variants in wild felids from Kenya - Githaka, Naftaly W.; Konnai, S.; Kariuki, E.; Kanduma, Esther G.; Murata, S.; Ohashi, K. (Elsevier, 2012)
Piroplasms frequently infect domestic and wild carnivores. At present, there is limited information on the occurrence and molecular identity of these tick-borne parasites in wild felids in Kenya. In 2009, a pair of captive lions (Panthare leo) was diagnosed with suspected babesiosis and mineral deficiency at an animal orphanage on the outskirts of Nairobi, Kenya. Blood smears indicated presences of haemoparasites in the erythrocytes, however, no further investigations were conducted to identify the infecting agent. The animals recovered completely following diet supplementation and treatment with anti-parasite drug. In this report, we extracted and detected parasite DNA from the two lions and seven other asymptomatic feline samples; two leopards (Panthera pardus) and five cheetahs (Acinonyx jubatus). Reverse line blot with probes specific for Babesia spp. of felines indicated the presence of new Babesia species or genotypes in the lions and leopards, and unknown Theileria sp. in the cheetahs. Phylogenetic analyses using partial sequences of 18S ribosomal RNA (18S rRNA) gene showed that the parasite infecting the lions belong to the Babesia canis complex, and the parasite variant detected in the leopards clusters in a clade bearing other Babesia spp. reported in wild felids from Africa. The cheetah isolates falls in the Theileria sensu stricto group. Our findings indicate the occurrence of potentially new species or genotypes of piroplams in all three feline species.